Effect of Water Volume and Vertical Pattern on Growth and Yield of Green Mustard (Brassica Juncea L.) - Arif Abdul Manan; Al Machfudz WDP (Universitas Muhammadiyah Sidoarjo, 2015)
This research aims to determine the effect of water volume and pattern vertikultur on growth and yield of green mustard (Brassica juncea L.). This research was conducted at Greenhouse, Faculty of Agriculture, Muhammadiyah University of Sidoarjo, from June to July 2011. The study was arranged in a factorial in a completely randomized design (CRD) with repeat 3 times; The first factor was the volume of water that consists of four levels, particulary 50 ml, 100 ml, 150 ml and 200 ml, and the second factor was vertikultur pattern consisting of three levels, particulary without vertikultur, vertikultur upright, and vertikultur sloping staircase. Data were analyzed using Analysis of Varian and further tested by LSD test with a level of 5% to determine differences between treatments. The results showed that the volume of water gives a real influence on the parameters of plant height, stem diameter, number of leaves, leaf area and plant fresh weight; whereas vertikultur patterns significantly affect plant height, leaf number, leaf area and fresh weight of mustard. The influence of the interaction between water volume and pattern apparently vertikultur against broad leaf mustard. The best treatment was obtained on the water volume of 100 ml with a pattern without vertikultur with an average wet weight is 46.13 g mustard plants.